2014
DOI: 10.1007/s12011-014-0121-6
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Metals in the Blood and Specific Porphyrins in the Urine in Children with Autism Spectrum Disorders

Abstract: The aim of the present study was to determine the levels of metals in blood (zinc (Zn), copper (Cu), aluminium (Al), lead (Pb) and mercury (Hg)), as well as the specific porphyrin levels in the urine of patients with autism spectrum disorder (ASD) compared with patients with other neurological disorders. The study was performed in a group of children with ASD (N = 52, average age = 6.2 years) and a control group of children with other neurological disorders (N = 22, average age = 6.6 years), matched in terms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(28 citation statements)
references
References 80 publications
0
26
0
2
Order By: Relevance
“…A recent study suggests that increased levels of BPb in some children with ASD may trigger the production of serum anti-ribosomal P antibodies (Mostafa et al 2016b). It has been reported that ASD children often have a lower zinc (Zn)-to-copper (Cu) ratio in blood compared to healthy controls (Faber et al 2009, Li et al 2014, Crăciun et al 2016) and children with other neurological disorders (Macedoni-Lukšič et al 2015). It has been suggested that metallothionein (MT) dysfunction may occur as a cause of Hg accumulation in children with ASD, and the same dysfunction may also lead to Zn deficiency (Bjørklund 2013).…”
Section: Autoantibodiesmentioning
confidence: 99%
“…A recent study suggests that increased levels of BPb in some children with ASD may trigger the production of serum anti-ribosomal P antibodies (Mostafa et al 2016b). It has been reported that ASD children often have a lower zinc (Zn)-to-copper (Cu) ratio in blood compared to healthy controls (Faber et al 2009, Li et al 2014, Crăciun et al 2016) and children with other neurological disorders (Macedoni-Lukšič et al 2015). It has been suggested that metallothionein (MT) dysfunction may occur as a cause of Hg accumulation in children with ASD, and the same dysfunction may also lead to Zn deficiency (Bjørklund 2013).…”
Section: Autoantibodiesmentioning
confidence: 99%
“…It should be emphasised that literature data underscore the Cu/Zn ratio as a potential blood biomarker of different health disorders. Thus, increased values of the Cu/Zn ratio were determined in developmental and behavioural disorders in children (52) and in some cases of cancer (53).…”
Section: Bulat Z Et Al Can Zinc Supplementation Ameliorate Cadmium-mentioning
confidence: 99%
“…Most studies have considered metal levels in blood, hair, and urine for those with diagnosed ASD compared to controls. This research has yielded inconsistent results with respect to Pb and Hg, with most studies finding non-significant differences (10, 11) or even a reduced level of some non-essential metals (Pb) in those with ASD (12). …”
mentioning
confidence: 99%